Anti-Inflammatory and Tissue Regenerative Effects of Topical Treatment with Ozonated Olive Oil/Vitamin E Acetate in Balanitis Xerotica Obliterans - Currò, Monica (Molecules, 2018)
Balanitis xerotica obliterans (BXO) is a chronic inflammatory skin disorder, considered the male genital variant of lichen sclerosus. Anti-inflammatory drugs are commonly used in BXO. We evaluated the effects of an innovative formulation of ozonated olive oil with vitamin E acetate (OZOILE(®)) on the inflammatory status and tissue remodeling in male children with BXO. The mRNA transcripts of proteins involved either in inflammation or in dynamics of tissue regeneration were analyzed by quantitative real-time PCR, in foreskins affected by BXO removed from patients untreated or treated with OZOILE(®) cream for 7 days before circumcision. We found a significant reduction in mRNA levels of IL-1β, TNF-α, INF–γ, transglutaminase 2 and NOS2 in foreskins treated with OZOILE(®) in comparison to untreated ones (p < 0.001). No significant differences were observed in NF-κB activation in the specimens obtained from treated and untreated patients. Hence, OZOILE(®) treatment up-regulated hypoxia-inducible factor (HIF)-1alpha, vascular endothelial growth factor (VEGF) and E-cadherin gene expression (p < 0.001). The treatment with OZOILE(®) showed effective results in children affected by BXO by reducing the inflammatory process and stimulating mechanisms for tissue regeneration of the foreskin. A randomized clinical trial on a large number of children affected by BXO might be useful to verify the efficacy of topical treatment with OZOILE(®).